2017
DOI: 10.1016/j.ijom.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite element model to predict patterns of pterygomaxillary dysjunction during Le Fort I osteotomy

Abstract: The aim of this study was to determine whether non-linear three-dimensional finite element analysis (3D-FEA) can be applied to simulate pterygomaxillary dysjunction during Le Fort I osteotomy (LFI) not involving a curved osteotome (LFI-non-COSep), and to predict potential changes in the fracture pattern associated with extending the cutting line. Computed tomography (CT) image data (100 snapshots) after LFI were converted to 3D-CT images. 3D-FEA models were built using preoperative CT matrix data and used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(49 reference statements)
0
5
0
3
Order By: Relevance
“…The rate of agreement between the FEA-predicted pterygomaxillary disjunction site and the actual disjunction site observed on postoperative CT images obtained 7 days after the LF1-non-COSep osteotomy with Tessier spreaders was 87%, which confirms that FEA has credibility in orthognathic surgery. Additionally, FEA demonstrated that the extension of the cutting line to the maxillary tuberosity was associated with a higher incidence of pterygoid process fractures [ 41 ], which is valuable information for clinicians.…”
Section: Orthognathic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of agreement between the FEA-predicted pterygomaxillary disjunction site and the actual disjunction site observed on postoperative CT images obtained 7 days after the LF1-non-COSep osteotomy with Tessier spreaders was 87%, which confirms that FEA has credibility in orthognathic surgery. Additionally, FEA demonstrated that the extension of the cutting line to the maxillary tuberosity was associated with a higher incidence of pterygoid process fractures [ 41 ], which is valuable information for clinicians.…”
Section: Orthognathic Surgerymentioning
confidence: 99%
“…In the presented literature, for the calculation of Young’s modulus, Szucs et al, Tamura et al and Fuji et al converted each pixel of the CT dataset from Grey to Hounsfield units and using equations dedicated to this subject, calculated Young’s modulus from the obtained bone density. This approach enables researchers to distinguish stronger and weaker structures of the maxillofacial skeleton and as a result to create more realistic models [ 13 , 36 , 41 ]. When it comes to limitations in the numerical model discretization encountered as a result of software, attention has been directed towards the selective increase of the numerical model mesh density in the precise region of the investigated area [ 63 ].…”
Section: Limitations and Future Outlookmentioning
confidence: 99%
“…In maxillofacial scenario, FEM has been used to determine the stability of internal fixation in implant surgery, 11 orthognathic surgery, 12 panfacial trauma11, 13, 14 and reconstruction procedures 15 . FEM has also been used effectively by numerous authors to compare the different types of plates in different fracture patterns of mandible.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted incidence of pterygoid process fracture was higher for cutting lines that extended to the pterygomaxillary junction than for conventional cutting lines. They also added that, 3-D FEA can be a useful tool in predicting pterygomaxillary dysjunction patterns and provides useful information in selecting safe procedures during LFI-non-COSep [57].…”
Section: Orthognathic Surgerymentioning
confidence: 99%